Basic bidding formats: Characteristics and differences - Fritz Helmedag (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2021)
In standard auction theory, the 'revenue equivalence theorem' asserts that the outcomes of the elementary allocation methods coincide. However, bidding processes differ fundamentally with regard to the decision situation of the participants: Is it at all imperative to take into consideration the number of competitors ('stochastic' strategy) or not ('deterministic' course of action)? Furthermore, established auction theory neglects the operating modes of procurement alternatives under uncertainty. Apart from the lacking knowledge how many rivals have to be beaten, tenderers regularly are ignorant of the buyer's reserve price. Then it is even more tentative to calculate an offer based on probability theory. Consequently, the suppliers' propensity to collude increases.
Keywords: D44; 330; Auctions; Tendering; Strategic Bidding